2022
DOI: 10.3389/fpls.2022.828729
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Native Photorespiration Gene Motifs of Promoter Untranslated Region Combinations Under Short Term Abiotic Stress Conditions

Abstract: Quantitative traits are rarely controlled by a single gene, thereby making multi-gene transformation an indispensable component of modern synthetic biology approaches. However, the shortage of unique gene regulatory elements (GREs) for the robust simultaneous expression of multiple nuclear transgenes is a major bottleneck that impedes the engineering of complex pathways in plants. In this study, we compared the transcriptional efficacies of a comprehensive list of well-documented promoter and untranslated regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 109 publications
1
12
0
Order By: Relevance
“…The obtained promoters possess different tissue-specific, strength, and inducibility properties, enabling the co-expression of numerous genes at different levels, as is required by the complex biosynthesis traits or regulatory circuits responding to various environmental conditions, i.e., biotic, abiotic, tissue-specific, light stress, or hormonal stimulation [184,185,[189][190][191][192][193][194]. To avoid unwanted recombination or homology-dependent gene silencing, the expression of each gene is regulated by a different promoter [189,195].…”
Section: Objectives and General Methodology Of Synthetic Promoter Cre...mentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained promoters possess different tissue-specific, strength, and inducibility properties, enabling the co-expression of numerous genes at different levels, as is required by the complex biosynthesis traits or regulatory circuits responding to various environmental conditions, i.e., biotic, abiotic, tissue-specific, light stress, or hormonal stimulation [184,185,[189][190][191][192][193][194]. To avoid unwanted recombination or homology-dependent gene silencing, the expression of each gene is regulated by a different promoter [189,195].…”
Section: Objectives and General Methodology Of Synthetic Promoter Cre...mentioning
confidence: 99%
“…Among the analyzed cis-responsive elements, MYB and b-ZIP reduced transgene expression rate, measured by luciferase activity, by recruiting transcriptional repressors. However, bHLH increased luciferase activity in response to elevated temperatures, and AP2 in response to high irradiance [192]. Studies on the role of UTR regions in plants and viruses suggest that plant-derived UTRs outperform viral UTRs under ambient conditions.…”
Section: Cis-element Juggling and Domain Swappingmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies have also shown the potential for fine‐tuning transgene expression levels by regulatory elements while spatiotemporal specificity is preserved [37,72,7779]. In order to achieve quantitative expression at various levels, a rational design by combining multiple regulatory elements from various species, such as the core promoters, enhancers, 5′UTR, 3′UTR, and introns, was used to construct expression cassettes with quantitative intensities in multiple species and tissues [54,57,68,80,81]. The theoretical transcriptional activity (TTA) of cassettes with different promoter/terminator combinations is coincident with the experimental activity values in transiently transformed Nicotiana leaves [56].…”
Section: Quantitative Plant Synthetic Biology Is Emergingmentioning
confidence: 99%
“…Therefore, in addition to the characterization of these elements, redesign new elements that can meet specific requirements is also an indispensable approach. Recent studies have also shown the potential for fine-tuning transgene expression levels by regulatory elements while spatiotemporal specificity is preserved [37, 72,[77][78][79]. In order to achieve quantitative expression at various levels, a rational design by combining multiple regulatory elements from various species, such as the core promoters, enhancers, 5′UTR, 3′UTR, and introns, was used to construct expression cassettes with quantitative intensities in multiple species and tissues [54,57,68,80,81].…”
Section: Quantitative Characterization Of Genetic Partsmentioning
confidence: 99%